The effects of various parameters on the accuracy of kinematic PPP in different platforms - Gurturk, Mert; Soycan, Metin (YILDIZ TECHNICAL UNIV, 2022)
The Precise Point Positioning (PPP) technique has become an alternative to relative point positioning techniques in the evaluation of Global Navigation Satellite System (GNSS) data because of its less labor and cost-effectiveness. However, there are many parameters ( integer ambiguity resolution, satellite geometry, filter type, atmospheric delays, satellite clock offsets and frequency types) to consider in kinematic PPP and these can have different effects on different platforms. This study, therefore, investigated the effects of various parameters on the accuracy and convergence time of kinematic PPP in different platforms. 3-hour GNSS data, acquired simultaneously from two different receivers (mounted on static and moving platforms), were evaluated using the Kinematic PPP method with different processing parameters in the following four scenarios: satellite combination and geometry, tropospheric model and clock product, all of which have effective roles to play in kinematic PPP processing. The results show that the effect of these parameters in terms of positioning accuracy were, in descending order, strongest for: satellite combination, satellite geometry, troposphere correction, and clock product scenarios. Notably, in the satellite combination scenarios, some parameters have negative effects of up to meter level in the moving receiver compared with the static receiver.
Keywords: GNSS; Kinematic PPP; Effective Parameters; Relative Point Positioning; POINT POSITIONING PPP; MULTI-GNSS; GPS; FREQUENCY; SERVICES; IMPACT; CLOCK; Engineering